Translation Techniques of Culture Specific Items Found in “Of Mice and Men” Novel and Their Impact on Readability - Permatahati, Martinda Intan; Faridi, Abdurrachman; Saleh, Mursid (International Journal of Active Learning, 2022)
The main activity of translation is transferring meaning from source language into target language. The strategy is used to translate will affect to the readability level. Cultural gaps between SL and TL have always turned to be a problem that is difficult to solve in translation. This article aims at finding the translation techniques that are applied in translating culture specific items (CSI) and explaining the readability level of translated novel in Of Mice and Men, entitled Tikus dan Manusia by Ariyantri E. Tarman. This research is descriptive qualitative. Data collection was done manually from the novel. Experts’ judgment will provide comments to maintain the validity of the data. Questionnaire helps to score the readability of the text. The theory of CSI proposed by Newmark (1998), the translation techniques by Davies (2003), The Automated Readability Index (ARI) Formula to find the match age in readability process, and Readability Rating Instrument by Nababan (2009) . This research finding shows that the translator tended to use translation techniques oriented to target language (TL). Thus, the priority of the translation work is it should be read by the ideal target readers. From the result, it can the technique used can get high level of readability for college graduate readers.